Discovery of long‐distance gamete dispersal in a lichen‐forming ascomycete - Ronnås, Cecilia (New Phytol, 2017)
Accurate estimates of gamete and offspring dispersal range are required for the understanding and prediction of spatial population dynamics and species persistence. Little is known about gamete dispersal in fungi, especially in lichen‐forming ascomycetes. Here, we estimate the dispersal functions of clonal propagules, gametes and ascospores of the epiphytic lichen Lobaria pulmonaria. We use hierarchical Bayesian parentage analysis, which integrates genetic and ecological information from multiannual colonization and dispersal source data collected in a large, old‐growth forest landscape. The effective dispersal range of gametes is several hundred metres to kilometres from potential paternal individuals. By contrast, clonal propagules disperse only tens of metres, and ascospores disperse over several thousand metres. Our study reveals the dispersal distances of individual reproductive units; clonal propagules, gametes and ascospores, which is of great importance for a thorough understanding of the spatial dynamics of ascomycetes. Sexual reproduction occurs between distant individuals. However, whereas gametes and ascospores disperse over long distances, the overall rate of colonization of trees is low. Hence, establishment is the limiting factor for the colonization of new host trees by the lichen in old‐growth landscapes.